Exposition of Some Reliable Principles of Theoretical Mysticism - Àyatullah Jawadi Àmuli (حکمت اسرا)
The paper in hand surveys a number of key ideas and benefits of theoretical mysticism vis-à-vis both conceptual or discursive knowledge and intuitive realization. For a clear exposition of the vantage point of theoretical mysticism and its role in appraising both discursive science and intuitive understanding, it is necessary to become acquainted with a number of rules and principles of theoretical mysticism. With a view to accomplishing this, this shortepistle, in nineteen parts, investigates some of the aforementioned rules and principles—both setting them out as well as referencing their sources; and in the process determining the role and position of theoretical mysticism in the midst of the intuitive and discursive modalities of apprehension.